Imaging ROMK1 inwardly rectifying ATP-sensitive K+ channel protein using atomic force microscopy. - Henderson, R M (1996)
The inwardly rectifying K+ channel ROMK1 has been implicated as being significant in K+ secretion in the distal nephron. ROMK1 has been shown by immunocytochemistry to be expressed in relevant nephron segments. The development of the atomic force microscope has made possible the production of high resolution images of small particles, including a variety of biological macromolecules. Recently, a fusion protein of glutathione S-transferase (GST) and ROMK1 (ROMK1-GST) has been used to produce a polyclonal antibody for immunolocalization of ROMK1. We have used atomic force microscopy to examine ROMK1-GST and the native ROMK1 polypeptide cleaved from GST. Imaging was conducted with the proteins in physiological solutions attached to mica. ROMK1-GST appears in images as a particle composed of two units of similar size. Analyses of images indicate that the two units have volumes of approximately 118 nm3, which is close to the theoretical volume of a globular protein of approximately 65 kDa (the molecular mass of ROMK1-GST). Native GST exists as a dimer, and the images obtained here are consistent with the ROMK1-GST fusion protein's existence as a heterodimer. In experiments on ROMK1 in aqueous solution, single molecules appear to aggregate, but contact to the mica was maintained. Addition of ATP to the solution produced a change in height of the aggregates. This change (which was reversible) suggests that ATP induces a structural change in the ROMK1 protein. The data show that atomic force microscopy is a useful tool for examination of purified protein molecules under near-physiological conditions, and furthermore, that structural alterations in the proteins may be continuously investigated.